On simulating shoreline evolution using a hybrid 2D/one-line model - Seenath, A (Elsevier, 2022)
Hybrid 2D/one-line shoreline models are becoming increasingly applied over the mesoscale (101–102 years; 101–102 km) to inform coastal management. These models typically apply the one-line theory to simulate changes in shoreline morphology based on littoral drift gradients calculated from a 2DH coupled wave, flow, and sediment transport model. However, the key boundary conditions needed to effectively apply hybrid 2D/one-line models and their applicability beyond simple planform morphologies are uncertain, which can potentially comprise coastal management decisions. To address these uncertainties, an extensive numerical modelling campaign is carried out to both assess the sensitivity and calibrate an advanced hybrid 2D/one-line model (MIKE21) against six variables in three different sandy coastal system morphologies: (a) a simple planform morphology with a gentle sloping profile, (b) a simple planform morphology with a steep sloping profile, and (c) a complex planform morphology. The six variables considered include nearshore discretisation, bathymetry, bed friction, sand grain diameter, sand porosity, sediment grading, and the weir coefficient of hard defence structures. Five key conclusions are derived from the sensitivity testing and calibration results. First, the optimal boundary conditions for modelling shoreline evolution vary according to coastal geomorphology and processes. Second, specifying boundary conditions within physically realistic ranges does not guarantee reliable shoreline evolution predictions. Third, nearshore discretisation should be treated as a typical calibration parameter as (a) the finest discretisation does not guarantee the most accurate predictions, and (b) defining a discretisation based on process length scales also does not guarantee reliable predictions. Fourth, hybrid 2D/one-line models are not valid for application in complex planform morphologies plausibly because of the one-line theory assumption of a spatially invariable closure depth. Fifth, hybrid 2D/one-line models have limited applicability in simple planform morphologies where the active beach profile is subject to direct human modification, plausibly due to the one-line theory assumption of a constant time-averaged coastal profile form. These findings provide key theoretical insights into the drivers of shoreline evolution in sandy coastal systems, which have practical implications for refining the continued application of shoreline evolution models.